CRISTIAN GĂZDAC, MARIN NEAGOE, WEALTHY OR NOT IN THE TIME OF TURMOIL? THE ROMAN IMPERIAL HOARD FROM GRUIA IN ROMAN DACIA (ROMANIA) - Răzvan Bogdan Gaspar (Journal of Ancient History and Archaeology)
Cristian Găzdac, Marin Neagoe, Wealthy or not in the time of turmoil? The Roman Imperial Hoard from Gruia in Roman Dacia (Romania), Archaeopress, Oxford, ISBN 978-1-78491